A organização textual da crônica de notícia - Gabriel Junior, Milton (2010)
This thesis is situated on Textual Linguistics and Critical Discourse Analysis with socio cognitive aspect, and it aims is to contribute to general studies of chronicle published in Brazilian newspapers. Specific objectives are: 1. Analyzing daily chronicle from the textual schema raised and organized by Gisele Scafuro in order to check which textual changes provide the text chronicles news 2) Describing the news textual chronicle scheme by its categories and their textual ordering rules, 3) Searching the textual construction s chronicler s opinion, 4) Analyzing the journalistic opinion on the news construction and its relations with the chronicler opinion, in order to privilege intertextual figures. The research is focus on national chronicle. Their structures are totally different from others and there is an originality that set them apart from other chronicle published in other countries. In Brazil, chronicle appears in the folhetim-variedade a kind a part of the newspaper that present varieties and entertainment, consolidating itself as a place where there are the heterogeneous tests, the novel, the prose poem. This mixture of genres that gives the Brazilian chronicle characteristic, turning into a specific genre. Progressively chronicles, as the newspaper, will specialize in specific section, gradually, the daily chronicle is modified in chronicles news, allowing the chronicler express his opinion about a fact reported in the newspaper. The analysis material was collected in the newspaper O Estado de S. Paulo, Folha de S. Paulo in their different sections. The methodological procedure is the theoretical analytical and its point of departure is the canonical categories of argumentative structure: premise, hypothesis, explanation and conclusion, thus they are the ones who organize an opinionated text. The results provided conclude that: 1. the chronicler s opinion presents similarity to the newspaper ideology company , but it presents dissimilarity to the journalistic news, 2. the opinion of the chronicler is constructed based on the Social Cognition, is routine or because reported 3. The textual categories establish a relationship between the unexpected news, the popular news already published and Social Cognitions